Psycap and Marketing Innovation Impact on Start up Sustainable Competitive Advantages in Adopting Technology Disruption - Ratih Hadiantini; Fitriani Reyta (Pusat Riset dan Inovasi Nasional, 2024)
The startup business in Indonesia has grown quite rapidly in recent years. However, there are a number of problems the startup faces. One of the various problems faced, are funding, infrastructure, mentor networks, markets and technology disruption. Technological disruption has succeeded in transforming old technology that previously used more physical to digital technology that can produce a number of completely new things, which are more useful and more efficient, in a short period of time. To absorb all changes from technological disruption, psychological capital is also needed to absorb all changes quickly. The need for psycap is motivated by the desire to make a profit and for the organization to remain competitive, so companies need to manage talent and train professionals to become better leaders and subordinates and to become employees who can think innovatively and contribute to achieving organizational goals. Observation and evaluation of changes in the dynamic corporate environment are essential inputs and sources for the development of a sustainable competitive advantage related to strategy in the field of marketing and in the area of strategic management. Thus, research on the concept of sustainable competitive advantage is needed in order to analyze the technology disruption impact on the suistainable competitive advantages stages of start up in Indonesia. This study examine how psycap and innovation in marketing impact on sustainable start-ups competitive advantage in Indonesia, 390 startup were taken as samples from 20.692 startup population in Bandung City, using quantitative method and partial least square, the result shown that 82,7% psycap and marketing innovation impact to startup sustainability competitive advantages in Bandung City, Indonesia.